A survey of corporate finance practices in micro-enterprises: an exploratory analysis conditional on firm and manager characteristics - Paulo Morais Francisco (Cogent Business & Management, 2024)
This study outlines the findings from a survey of 208 micro-enterprises (MEs) in Portugal, focusing on their corporate finance practices, including working capital management (WCM), financing and investment decisions, the adoption of accounting information systems (AIS) and the use of financial data. Both an unconditional exploratory study and a study conditional on the characteristics of the ME and its manager are conducted. The unconditional results reveal direct CEO involvement in cash management and accounts receivable in MEs. While these companies use AIS for financial reporting, the use of financial ratios is uncommon. Additionally, these MEs do not frequently calculate the cost of capital and primarily rely on the payback rule as an investment decision criterion. With respect to the conditional analysis, the results indicate that factors such as size and managers' education, especially in finance, significantly influence the sophistication of corporate finance functions. Moreover, management diversity emerges as a key driver across various financial functions, and family businesses demonstrate heightened concern for these financial aspects. The study concludes by recommending the promotion of financial education for ME managers to enhance their financial management practices. Particularly, it advocates for targeted financial literacy policies and training and the adoption of advanced financial tools to support the growth and sustainability of MEs.
Keywords: G31; G32; M21; M41; 650; Micro-enterprises; corporate finance; investment analysis; financial analysis; accounting systems